Interoperability Issues and Challenges in 6G Networks - Kharche, Shubhangi; Dere, Prajakta (Journal of Mobile Multimedia, 2022)
Interoperability allows seamless data exchange among the heterogeneous networks and is a crucial problem for the growth of forthcoming 6G networks. The research has focussed on the interoperability issues in the Internet of Things (IoT) related to cross-domain and cross-platform applications. However, the future 6G communication networks are not limited to interoperating with IoT. The 6G networks must interoperate with the Wearable IoT (WIoT), brain abstracted Internet of Thinking (IoTk), Internet of Everything, and other space and undersea networks. The network softwarization, slicing, and intelligentization techniques are envisioned to support seamless data exchange between 6G and other heterogeneous networks. However, to successfully achieve the goal of global 360<span id="MathJax-Element-1-Frame" class="MathJax" style="display: inline; font-style: normal; font-weight: 400; line-height: normal; font-size: medium; text-indent: 0px; text-align: left; text-transform: none; letter-spacing: normal; word-spacing: 0px; overflow-wrap: normal; white-space: nowrap; float: none; direction: ltr; max-width: none; max-height: none; min-width: 0px; min-height: 0px; border: 0px; padding: 0px; margin: 0px; color: #000000; font-family: 'Times New Roman'; font-variant-ligatures: normal; font-variant-caps: normal; orphans: 2; widows: 2; -webkit-text-stroke-width: 0px; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; position: relative;" tabindex="0" role="presentation" data-mathml="∘">∘∘ connectivity in 3D space, interoperability issues with heterogeneous services, applications, protocols, networks, etc., must be solved. The integration and interoperability of 6G networks with all aforementioned heterogeneous networks are inevitable to realize the goals of 3D communication successfully. The paper proposes a taxonomy to provide deep insights into interoperability issues, challenges, and possible solutions for 6G interoperability with WIoT, IoTk, IoE, and other networks. Though the techniques mentioned above in 6G networks will allow interoperable solutions, the integration and interoperability issues persist due to heterogeneities in high-frequency bands, base stations, technologies, device identities, protocols, and interfaces. The paper summarizes significant challenges regarding interoperability issues in various areas related to 6G and highlights the broad scope to further research.